Does transcutaneous electrical nerve stimulation have an antipruritic effect in lichen planus? A randomized clinical trial. (26th June 2018) - Waked, I.; Ibrahim, Z.; Elgohary, H. M. I.
Summary: Background: Lichen planus (LP) is a moderately prevalent inflammatory disorder that affects the skin and the oral mucosa, leading to a characteristic appearance and causing severe itching. Aim: To assess the potency of transcutaneous electrical nerve stimulation (TENS) as an antipruritic line of treatment in patients with LP. Methods: We enrolled 30 patients with LP who had a history of recurrent relapses of confined pruritus forcing them to scratch or rub the affected area intensively. Patients were treated with TENS three times per week for 4 weeks. Severity of itching was estimated by visual analogue scale (VAS) and Dermatology Life Quality Index (DLQI). Results: There was a statistically significant decline in mean VAS score at weeks 2 and 4 of treatment compared with baseline ( P  < 0.05, with 74% of participants having an improvement of > 50%. Significant improvement in itching intensity also resulted in better quality of life, as there was also a significant reduction in median DLQI at weeks 2 and 4 of therapy compared with baseline ( P  < 0.05), with 65% of patients having an improvement of > 50% in median DLQI score. Conclusion: TENS may be an alternative safe treatment for LP‐induced itching.